RELASI AGAMA DAN NEGARA DALAM PERSPEKTIF ISLAM - Zaprulkhan Zaprulkhan (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
One discourse that continues to be discussed in the realm of Islamic political philosophy is about the relation between religion and state. Broadly speaking, there are at least three paradigms of thinking about the relationship between religion and state. First, the secularistic paradigm, which says that Islam has nothing to do with the state because Islam does not regulate state life or reign. Second, the formalistic paradigm, which assumes that Islam is a complete religion, which includes everything, including the question of the state or a political system. Third, paradigms are substantialistic, which rejects the notion that Islam covers everything and also rejects the nation that Islam only governs the relationship between man and his Creator alone. This article will take pictures of how the three views of this paradigm by showing some of the characters are representative and critically using the comparative method.